Relationship between Serum Level and Gene Expression of IL-18 in Recurrent Miscarriage Iraqi Women Infected with Toxoplasmosis - Fadhil, Sabreen Hadi; Saheb, Entsar Jabbar (Iraqi Journal of Science, 2024)
Infectious toxoplasmosis, caused by an obligate intracellular protozoan Toxoplasma gondii, is a prevalent zoonotic disease that affects humans and warm-blooded animals. Cytokines are a class of signaling molecules that are widely employed in cellular communication; cells produce them, and they have an impact on how other cells interact. The aim of this study was to clarify the relationship between serum levels and gene expression of interleukin18 in miscarried women with toxoplasmosis. A Total of 200 blood samples from patients and controls were collected from Baghdad, Iraq between November 2021 and March 2022 which were used to measure gene expression of IL-18 using real-time PCR. Enzyme-linked immunosorbent assay was used to detect the level of IL-18. The findings of this investigation showed that the IL-18 serum concentration elevated significantly in healthy pregnant women compared to women with recurrent miscarriage and toxoplasmosis, recurrent miscarriage without toxoplasmosis and healthy women. Also, women who had recurrent miscarriage with toxoplasmosis showed significant differences compared with women who had recurrent miscarriage as well as healthy women (p< 0.005). Additionally, significant differences between patient and control were revealed by gene expression data. Also, there was statistically positive correlation between toxoplasmosis and IL-18 gene expression in the patient group. The IL-18 gene expression provided sensitive and precise toxoplasmosis diagnosis. Summing everything it can be concluded that serum level and gene expression of IL-18 elevated in recurrent miscarriage women infected with toxoplasmosis in comparison with other studied groups. Thus, the expression of IL-18 gene could serve as an indicator for women with miscarriage and toxoplasmosis.